Placental‐Specific Overexpression of sFlt‐1 Alters Trophoblast Differentiation and Nutrient Transporter Expression in an IUGR Mouse Model. Issue 6 (10th January 2017) - Kühnel, Elisabeth; Kleff, Veronika; Stojanovska, Violeta; Kaiser, Stephanie; Waldschütz, Ralph; Herse, Florian; Plösch, Torsten; Winterhager, Elke; Gellhaus, Alexandra
ABSTRACT: Since it is known that placental overexpression of the human anti‐angiogenic molecule sFlt‐1, the main candidate in the progression of preeclampsia, lead to intrauterine growth restriction (IUGR) in mice by lentiviral transduction of mouse blastocysts, we hypothesize that sFlt‐1 influence placental morphology and physiology resulting in fetal IUGR. We therefore examined the effect of sFlt‐1 on placental morphology and physiology at embryonic day 18.5 with histologic and morphometric analyses, transcript analyses, immunoblotting, and methylation studies. Interestingly, placental overexpression of sFlt‐1 leads to IUGR in the fetus and results in lower placental weights. Moreover, we observed altered trophoblast differentiation with reduced expression of IGF2, resulting in a smaller placenta, a smaller labyrinth, and the loss of glycogen cells in the junctional zone. Changes in IGF2 are accompanied by small changes in its DNA methylation, whereas overall DNA methylation is unaffected. In addition, the expression of placental nutrient transporters, such as the glucose diffusion channel Cx26, is decreased. In contrast, the expression of the fatty acid transporter CD36 and the cholesterol transporter ABCA1 is significantly increased. In conclusion, placental sFlt‐1 overexpression resulted in a reduction in the differentiation of the spongiotrophoblast into glycogen cells. These findings of a reduced exchange area of the labyrinth and glycogen stores, as well as decreased expression of glucose transporter, could contribute to the intrauterine growth restriction phenotype. All of these factors change the intrauterine availability of nutrients. Thus, we speculate that the alterations triggered by increased anti‐angiogenesis strongly affect fetal outcome and programming. J. Cell. Biochem. 118: 1316–1329, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Mouse placenta‐specific overexpression of human sFlt‐1 resulted in IUGR characterized by an altered differentiation of the placental compartment, characterized by reductions in the placental labyrinthine area, as the nutrient exchange unit, and in the trophoblast giant cells C‐TGCs and SpA‐TGCs. In addition, our results indicate that a loss of glycogen cells as an energy store and producer of IGF2 for fetal and placental growth, the reduced expression of Cx26 and Glut1 for glucose uptake, and the increased expression of the fatty acid transporter CD36 could be the reason for IUGR.